Gambaran Perilaku Masyarakat Dalam Pengelolaan Sampah Rumah Tangga di Desa Orobatu - Fitra, Cahya; H, Miftah Chairani; Akbar, Fajar; Mappau, Zrimurti (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2025)
West Sulawesi National Waste Management Information Site (SIPSN). Household waste tops the list of waste sources with 40.78% in 2021 (Akbar, 2023). The amount of waste generation cannot be separated from the economic situation, welfare, consumption patterns, security patterns and community behavior, or the habit of people littering around their place of residence. This is related to the lack of public knowledge on how to manage household waste properly and correctly (Marpaung et al., 2022). As a result of people's habit of throwing garbage. Lack of awareness of the importance of cleanliness is the most important factor, in addition to the community's sensitivity to the environment must be questioned. They do not know what dangers will occur if they cannot protect the surrounding environment. (Yuniarti et al., 2020). This study was conducted to determine the description of community behavior in household waste management. The research method used in the study was descriptive method. The data collection technique is Simple Random Sampling or randomizing. Population to households in Orobatu Village, Tapalang Subdistrict with 331 households, as many as 181 samples. The results of the research that has been done show that the level of community knowledge related to household waste management is still lacking is 55.2%. Community attitudes related to household waste management are still lacking is 53.6%, and community actions related to household waste management are still lacking is 56.9%. The conclusion from the results of the study can be seen from the behavior of the community towards household waste management is still lacking. Suggestions from the research are to provide counseling to the community, especially regarding the management of organic and inorganic waste. The village cooperates with the Environmental Agency to prepare Waste Disposal Sites (TPS).